Triglyceride to HDL cholesterol ratio and risk for gestational diabetes and birth of a large-for-gestational-age newborn - Shahnaz Barat; Zohreh Batebi; Zinatossadat Bouzari; Azita Ghanbarpour (Babol University of Medical Sciences, 2018)
Background: Using oral glucose for glucose challenge test (GCT) and glucose tolerance test (GTT) is problematic, especially in early pregnancy when the pregnant woman is experiencing gastrointestinal complications. This research seeks to investigate the relationship between the ratio of Triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) and the risk of gestational diabetes and large for gestational age (LGA) fetus for suggesting a more appropriate index for diagnosis of gestational diabetes. Methods: The present cross-sectional study investigated pregnant women visiting the Perinatal Clinic of Ayatollah Rouhani Hospital in Babol for prenatal care from September 2015-2016. The GCT was performed on these pregnant women at 24-28 weeks as a screening test and their lipid profile, including HDL-C and TG, was simultaneously assessed after eight to 14 hours of fasting. Results: Significant differences were observed between women with and without gestational diabetes in terms of mean triglyceride, HDL, LDL/HDL ratio, triglyceride/LDL ratio and triglyceride/HDL ratio. The cut-off point of TG/HDL in the GTT was 4.254 with a sensitivity of 79.07% and specificity of 78%. Conclusions: According to the results obtained, lipid profile can help predict the risk of gestational diabetes, especially TG/HDL ratio that has a high sensitivity to diagnose gestational diabetes, while, lipid indices could not predict birth of a LGA neonate. Keywords: Gestational Diabetes, Triglyceride, Cholesterol, Triglyceride/HDL Ratio, Risk